2006
DOI: 10.2527/jas.2005-677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of milk somatic cells as a source of mRNA for study of lipogenesis in the mammary gland of lactating beef cows supplemented with dietary high-linoleate safflower seeds1

Abstract: Our objectives were 2-fold: to determine the effect of dietary linoleate on milk fat composition and on transcript abundance of acetyl-CoA carboxylase (ACC), fatty acid synthase (FAS), lipoprotein lipase (LPL), and stearoyl-CoA desaturase (SCD) mRNA in mammary tissue, and to evaluate milk somatic cell mRNA as a source of mammary tissue mRNA for these enzymes. Eighteen primiparous, crossbred beef cows (BW = 411 +/- 24 kg; BCS = 5.25) were offered Foxtail millet hay at 1.68% of BW daily and either a low-fat cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 34 publications
3
54
1
1
Order By: Relevance
“…It has been reported that milk somatic cells are viable (Feng et al, 2007) and that more than 90% of MEC are viable (Thompson et al, 1998). In addition, previous studies have shown that milk cell transcripts well represent the mammary tissue in bovine (Hayashi et al, 2004;Murrieta et al, 2006) and in caprine species . Moreover, in a recent experiment, we compared the use of milk MEC and biopsy during ODM and we found the same downregulation of genes involved in milk synthesis using both methods .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been reported that milk somatic cells are viable (Feng et al, 2007) and that more than 90% of MEC are viable (Thompson et al, 1998). In addition, previous studies have shown that milk cell transcripts well represent the mammary tissue in bovine (Hayashi et al, 2004;Murrieta et al, 2006) and in caprine species . Moreover, in a recent experiment, we compared the use of milk MEC and biopsy during ODM and we found the same downregulation of genes involved in milk synthesis using both methods .…”
Section: Discussionmentioning
confidence: 89%
“…Sampling of the tissues after slaughter or by using a biopsy needle are ways of collecting MEC, but these techniques are invasive. The collection of MEC from milk is a non-invasive alternative, which was previously used to study mammary gene expression in cows (Hayashi et al, 2004;Murrieta et al, 2006) and in goats ). An improvement in the method was developed in cows, consisting of the specific purification of MEC from somatic milk cells using magnetic beads (Boutinaud et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…FO is more effective than plant oils in elevating milk fat cis-9,trans-11-CLA content (Offer et al, 1999) because of the inhibitory effect of docosahexaenoic acid (DHA) in FO on VA reduction to stearic acid in the rumen (Boeckaert et al, 2008). These increases in milk cis-9,trans-11-CLA and trans-11-18:1 can be further enhanced when FO is provided in combination with plant oils or oilseeds rich in 18:2n-6 (Whitlock et al, 2002;AbuGhazaleh et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on the effect of nutrition on mammary lipid metabolism have been carried out using mammary tissue collected at the time of slaughtering or by biopsy, while only a few studies have been reported using milk cells from ruminants as a non-invasive method (Boutinaud et al, 2002 andMurrieta et al, 2006, Feng et al, 2007. The second aim of the present study was to investigate the effect of lipid-supplemented diets on the amount of milk purified mammary epithelial cells (MEC) and on the gene expression of lipogenic enzymes from MEC.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the invasive effect of the study we should minimise the number of mammary biopsy collection and chose other techniques especially for kinetic studies. The collection of MEC from milk is a non-invasive method that has been used previously to study mammary gene expression in cows (Hayashi et al, 2004;Murrieta et al, 2006;Boutinaud et al, 2008) and in goats (Boutinaud et al, 2002;Ben Chedly et al, 2011). The use of this technique avoids the carryover effect of sampling that may be observed in mammary biopsies.…”
Section: Introductionmentioning
confidence: 99%